Interactive narrative design for geolocated experiences - López-Arcos, José R; Gutiérrez Vela, Francisco L; Padilla-Zea, Natalia; Paderewski-Rodríguez, Patricia (ACM International Conference Proceeding Series Interaccion 2016, 2020)
Current computation paradigms allow us to interact with the technology through several devices at the same time. Virtual tools and interfaces belong to the real world. This is the reason why the number of pervasive and geolocated games has been increased. This kind of games mixes activities in the real world with technology typical from video games. These characteristics offer new challenges when designing interactive experiences and they give new ways of teaching through technology. Stories help to motivate participants. However, designing stories for video games is a hard task, due to the interactive characteristic of this media. Players can change the story flow with their own actions. Thus, writers and designers of the game must find the balance between the freedom of the player and the control of the quality of the story. In the present work, we propose a set of technics to design and evaluate a story aimed to lead a geolocated educational experience.
Conferencia de "17th International Conference on Human Computer Interaction, Interaccion 2016; Salamanca; Spain; 13 September 2016 through 16 September 2016"
Keywords: educational video games; geolocated experiences; methodology; narrative; storytelling; Scopus(2); WOS(2)